Transection of Radioactive Seeds in Breast Specimens. (October 2016) - Gilcrease, Michael Z.; Dogan, Basak E.; Black, Dalliah M.; Contreras, Alejandro; Dryden, Mark J.; Jimenez, Sandra M.
Abstract : Radioactive seed localization is a new procedure for localizing breast lesions that has several advantages over the standard wire-localization procedure. It is reported to be safe for both patients and medical personnel. Although it is theoretically possible to transect the titanium-encapsulated seed while processing the breast specimen in the pathology laboratory, the likelihood of such an event is thought to be exceedingly low. In fact, there are no previous reports of such an event in the literature to date. We recently encountered 2 cases in which a radioactive seed was inadvertently transected while slicing a breast specimen at the grossing bench. In this report, we describe each case and offer recommendations for minimizing radioactive exposure to personnel and for preventing radioactive contamination of laboratory equipment.